Interference of Salmonella enteritidis and Lactobacillus spp. with IL-8 levels and transepithelial electrical resistance of enterocyte-like Caco-2 cells - Fajdiga, S; Koninkx, J F J G; Tooten, P C J; Marinsek-Logar, R (Folia microbiologica, 2006)
Caco-2 cells (exhibiting characteristics of mature villus enterocytes) were used to determine bacteria (Salmonella enteritidis causing human gastroenteritis)-intestinal cell interactions. The interference of bacteria with the transepithelial electrical resistance (TEER) of filter-grown Caco-2 cells and the production of IL-8 after exposure of the cells to S. enteritidis 857 and/or Lactobacillus strains (L. gasseri LF221 and L. rhamnosus BGT10) was evaluated. The strain 857 decreased TEER of filter-grown Caco-2 cells; in contrast, lactobacilli had a little or no effect. The effect of S. enteritidis on the TEER decreased if Caco-2 cells were pre-incubated with lactobacilli. This strain induced high levels of IL-8 (which can lead to cell damage). Compared to the IL-8 synthesis after exposure of Caco-2 cells to S. enteritidis 857, simultaneous exposure of Caco-2 cells to S. enteritidis and lactobacilli inhibited the IL-8 synthesis after short recovery periods.
Keywords: interleukin-8; Lactobacillus; Salmonella Infections; Caco-2 buňky; Electric Impedance; střevní sliznice; Salmonella enteritidis; Immunity, Mucosal; lidé; Caco-2 Cells; Intestinal Mucosa; Humans; slizniční imunita; Interleukin-8; elektrická impedance; salmonelóza